Van A Gene for Intestinal Bacteria Enterococcus faecium (E. faecium) Resistant to Vancomycin - Venus H. Al-Saffar (Journal of Global Pharma Technology, 2016)
Out of 100 enterococcal strains clinical samples, a total of 59 (59%) Enterococcus faecium (E. faecium), 32 (32%) E. faecalis, 3 (3%) each of  E. casseliflavus, and E. avium, and 1 (1%) each of E. gallinarum, E. flavescens, and E. raffinosus  isolates were recovered, from burn, wound, and urine samples in Al-Hilla teaching hospital were identified to species level with a VITEK-2 system. For detection vancomycin resistance, all of enterococcus spp. isolates were tested by using multiplex PCR for (VanA, VanB, and Van C) genes. Results showed that only 5 isolates were resistant to vancomycin; 2 (VanA) genes were from E. faecium, 2 (VanB) genes were from E. faecalis, 1 (VanC) gene was from E. gallinarum.Keywords: VITEK-2, PCR.